"Doing Gender" and "Doing Religion" in Science: A Cross‐National Examination. Issue 2 (28th April 2020) - Thomson, Robert A.; Mehta, Sharan Kaur; Ecklund, Elaine Howard
Abstract: Women tend to be both underrepresented in science and overrepresented in organized religion, yet the connection between these two phenomena is rarely examined. With survey data collected among 6, 537 biologists and physicists from four national contexts—the United States, the United Kingdom, Italy, and India—we test whether science as a social field shapes religious expressions and attitudes differently for men and women. Findings reveal a religious gender gap in India and Italy but not in the United States and the United Kingdom. Further, except in Italy, men had higher odds of perceiving religion and science to be in conflict, believing that their colleagues have a negative attitude about religion, and reporting that science made them less religious. Evidence suggests that men in science may disproportionately internalize normative pressures to masculinize by eschewing religion. Our findings have implications for selection into academic science and the practice of religion among men and women in science.